Tor-Tor Raja-Raja sebagai Identitas Budaya Masyarakat Jorong Silayang Kecamatan Ranah Batahan Kabupaten Pasaman Barat - Zahratun Nisa; Hardi Hardi; Auliana Mukhti; Oktavianus Oktavianus (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This research aims to examine Tor-tor Raja-Raja as the cultural identity of the Mandailing community in Jorong Silayang, Ranah Batahan District, West Pasaman Regency. This study employed a qualitative method with a descriptive approach to describe factually the existence and implementation of Tor-tor Raja-Raja in community life. The theories used in this research are cultural identity theory by Alo Liliweri and Jonathan Rutherford, as well as performance structure theory by R. M. Soedarsono. Data collection techniques included observation, interviews, and documentation involving traditional leaders, artists, and local community members. The results show that Tor-tor Raja-Raja is a cultural identity passed down from generation to generation and is still preserved today. This dance is characterized by performers from traditional leadership groups or kings, an odd number of dancers, and performances limited to certain traditional ceremonies such as weddings and welcoming honored guests. Furthermore, Tor-tor Raja-Raja functions as a means of respect, reinforcement of customary values, and social communication within Mandailing society.